The potential benefits of radiotherapy in elderly patients with early-stage triple-negative breast cancer - Xu, Zheng; Qin, Chengdong; Cao, Binxiao; Ruan, Pengcheng; Zhang, Mianhao; Chen, Guidong (Frontiers in Medicine, 2025)
BackgroundBreast cancer (BC) is the most common cancer in women in the U.S. and a leading cause of cancer-related deaths. The incidence rises with age, especially in women over 70. Older patients often face multiple comorbidities, complicating treatment decisions. This study will analyze the role of radiotherapy (RT) in early-stage triple-negative breast cancer (TNBC) among elderly patients using the SEER database to assess its impact on survival outcomes.MethodsThe patients aged 70+ with T1-2N0-1M0 TNBC were selected from the SEER database (2010–2015) according to specific inclusion and exclusion criteria. Statistical analyses involved chi-square tests, propensity score matching (PSM), and Cox regression to identify risk factors. A nomogram was developed, and Kaplan-Meier analysis compared overall (OS) and breast cancer-specific survival (BCSS) across different groups.ResultsA total of 3,024 elderly patients with early-stage TNBC were analyzed. After employing PSM to eliminate baseline differences, survival analysis indicated that the breast-conserving surgery (BCS) group could benefit from RT (OS, HR = 0.68, p < 0.001; BCSS, HR = 0.64, p = 0.001). Cox regression analysis on the non-RT cohort within the BCS group identified age, tumor grade, and T stage as independent risk factors. Subsequently, a nomogram was developed to stratify patients and found that RT significantly improved OS and BCSS in the intermediate-risk (OS, HR = 0.49, 95% CI = 0.34–0.71, p = 0.001; BCSS, HR = 0.40, 95% CI = 0.21–0.77, p = 0.018) and high-risk group (OS, HR = 0.67, 95% CI = 0.55–0.81, p < 0.001; BCSS, HR = 0.61, 95% CI = 0.45–0.83, p = 0.007), while showing no significant benefit in the low-risk group (all p-values > 0.05).ConclusionRT significantly improves OS and BCSS in early-stage TNBC patients after BCS, particularly for intermediate to high-risk individuals, while low-risk patients may omit it.